2021
DOI: 10.3389/fimmu.2021.760707
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Induces Mitochondrial Compromise in CD4 T Cells From Chronically HCV-Infected Individuals

Abstract: We have previously shown that chronic Hepatitis C virus (HCV) infection can induce DNA damage and immune dysfunctions with excessive oxidative stress in T cells. Furthermore, evidence suggests that HCV contributes to increased susceptibility to metabolic disorders. However, the underlying mechanisms by which HCV infection impairs cellular metabolism in CD4 T cells remain unclear. In this study, we evaluated mitochondrial mass and intracellular and mitochondrial reactive oxygen species (ROS) production by flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 71 publications
2
11
0
Order By: Relevance
“…We have previously reported that chronic viral infection induces T cell aging and immune senescence due to accelerated telomeric DNA damage and mitochondrial dysfunction ( Yao and Moorman, 2013 ; Shi et al., 2014 ; Li et al., 2015 ; Zhou et al., 2016 ; Nguyen et al., 2018 ; Zhao et al., 2018 ; Cao et al., 2019 ; Ji et al., 2019 ; Zhao et al., 2019 ; Dang, 2020 ; Khanal et al., 2020 ; Schank et al., 2020 ; Khanal et al., 2021 ; Nguyen L. N. et al., 2021 ; Nguyen L. N. N. T. et al., 2021 ; Schank et al., 2021 ; Schank et al., 2021 ; Wang et al., 2021 ; Zhao et al., 2021 ; Cao et al., 2022 ). Given the crucial role of DNA topology in maintaining mitochondrial integrity and cell function and viability ( Champoux, 2001 ; Wang, 2002 ; Vos et al., 2011 ), here we sought to determine the levels of Top1 protein in the mitochondria of CD4 T cells from chronically HCV- or HIV-infected patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that chronic viral infection induces T cell aging and immune senescence due to accelerated telomeric DNA damage and mitochondrial dysfunction ( Yao and Moorman, 2013 ; Shi et al., 2014 ; Li et al., 2015 ; Zhou et al., 2016 ; Nguyen et al., 2018 ; Zhao et al., 2018 ; Cao et al., 2019 ; Ji et al., 2019 ; Zhao et al., 2019 ; Dang, 2020 ; Khanal et al., 2020 ; Schank et al., 2020 ; Khanal et al., 2021 ; Nguyen L. N. et al., 2021 ; Nguyen L. N. N. T. et al., 2021 ; Schank et al., 2021 ; Schank et al., 2021 ; Wang et al., 2021 ; Zhao et al., 2021 ; Cao et al., 2022 ). Given the crucial role of DNA topology in maintaining mitochondrial integrity and cell function and viability ( Champoux, 2001 ; Wang, 2002 ; Vos et al., 2011 ), here we sought to determine the levels of Top1 protein in the mitochondria of CD4 T cells from chronically HCV- or HIV-infected patients.…”
Section: Resultsmentioning
confidence: 99%
“…T cells play a critical role in controlling viral infections; however, the molecular mechanisms that dampen their responses during viral infections remain incompletely understood. We have recently reported that chronic viral (HCV, HIV) infection can cause T cell aging, as evidenced by the increases in the aging markers, telomeric and mitochondrial DNA damage, and mitochondrial dysfunction ( Yao and Moorman, 2013 ; Shi et al., 2014 ; Li et al., 2015 ; Zhou et al., 2016 ; Nguyen et al., 2018 ; Zhao et al., 2018 ; Cao et al., 2019 ; Ji et al., 2019 ; Zhao et al., 2019 ; Dang, 2020 ; Khanal et al., 2020 ; Schank et al., 2020 ; Khanal et al., 2021 ; Nguyen L. N. et al., 2021 ; Nguyen L. N. N. T. et al., 2021 ; Schank et al., 2021 ; Schank et al., 2021 ; Wang et al., 2021 ; Zhao et al., 2021 ; Cao et al., 2022 ). Mitochondria are important cellular organelles responsible for energy production and oxidative metabolism and are a major source of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of CPT1A can reduce mitochondrial respiration by about 50% in early exhausted T cells, suggesting early exhausted T cells switch the energy pathway to FAO when glycolysis is restricted ( 27 , 68 ). In addition, enhanced expression of PD-1 in exhausted T cells can also promote mitochondrial depolarization by reducing the transcriptional expression of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1α), a key transcriptional regulator involved in the regulation of energy generation and mitochondrial biogenesis genes, and mitochondrial transcription factor A (mtTFA) ( 68 , 73 ). Overexpression of PGC1α can promote metabolic fitness by enhanced glycolysis and mitochondrial respiration, and reduce depolarized mitochondria the in early exhausted T cells ( 17 , 27 , 68 , 73 ).…”
Section: Metabolic Dysfunction In T-cell Exhaustionmentioning
confidence: 99%
“…In addition, enhanced expression of PD-1 in exhausted T cells can also promote mitochondrial depolarization by reducing the transcriptional expression of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1α), a key transcriptional regulator involved in the regulation of energy generation and mitochondrial biogenesis genes, and mitochondrial transcription factor A (mtTFA) ( 68 , 73 ). Overexpression of PGC1α can promote metabolic fitness by enhanced glycolysis and mitochondrial respiration, and reduce depolarized mitochondria the in early exhausted T cells ( 17 , 27 , 68 , 73 ). Recent studies also revealed that continuous TCR stimulation under hypoxia promoted expression of Blimp-1, another transcriptional repressor of PGC1α, which induced the exhaustion of CD8 + T cells by repressing PGC1α-dependent mitochondrial reprogramming ( 74 , 75 ).…”
Section: Metabolic Dysfunction In T-cell Exhaustionmentioning
confidence: 99%